Perception And Knowledge Regarding Reproductive Health Among Adolescent Males Of Lalitpur - Upadhyay-Dhungel, Kshitiz; Dhungel, BA; Das, PKL; Karki, BMS (Asian Journal of Medical Sciences, 2013)
Background: Puberty is a significant phase of human growth. It has important implications for the development of regulatory competence and of physical, emotional, social maturity. Adolescents should have knowledge regarding their physical growth and reproductive health, so that unnecessary reservations and stress could be avoided. Adolescent males have as many health issues as adolescent females, but they are less likely to be seen in a clinical setting due to both individual factors and the health care system itself. Also, very few studies are done to access knowledge and perception of adolescent males regarding reproductive health. Hence, this study was designed to access the knowledge and perception of young adolescent males regarding physical growth and reproductive health which will help to design effective interventions mostly in terms of sex and health education. Method: : A Self designed questionnaire was given to the participants after explaining the objective of the study and taking written consent .The data was tabulated and students’ perception and knowledge regarding reproductive health was analysed. Result: 125 boys filled the form, mean age 13.2±2.2. Overall knowledge and perception regarding reproductive health was found to be satisfactory. Some shortcomings do exist like 50% participants did not know about contraceptives, 23% are worried about shape and size of their penis, and 23% feel no one understands them. Conclusion: Adolescent possess some knowledge about reproductive health but still effective educational intervention is required to encourage more sensible and healthy behaviour which and may lessen stress and reservations that comes with pubertal maturation. Asian Journal of Medical Science, Volume-3 No-3 (2012), Page -27-31 DOI: http://dx.doi.org/10.3126/ajms.v3i3.7744